Science and technology for development : Report on the united nation conference on the application of science and technology for the benefit of the less developed areas ; Vol. II Natural resources - United Nations (1963)
This report gives a narrative account of the United Nations conference on the application of science and technology for the benefit of the less developed areas.
Vol. II. Natural resources
Including bibliographical references and index
osa; 19/10/18
Loans
Keywords: Natural resources; Economic planning; Development